Entrepreneurship as a pathway to economic empowerment for ethnic minority women in Vietnam - Nam, Nguyen Thanh; Thanh, Nguyen Nghi (Journal of Asian Scientific Research, 2025)
This study explores the relationship between entrepreneurship and the economic empowerment of ethnic minority women in Vietnam, aiming to identify the key factors driving their entrepreneurial success. Using Structural Equation Modeling (SEM), the study examines how cultural traditions, market dynamics, empowerment through entrepreneurship, support networks, and ethical business practices influence economic empowerment. Cultural traditions emerged as a significant driver of economic empowerment, while market dynamics had a less pronounced impact. Entrepreneurship functions as both a source of income and a vehicle for personal and social empowerment. Support networks and ethical business practices are crucial in enabling inclusive economic participation. A reinforcing loop was identified, wherein empowerment led to sustained entrepreneurial engagement. Entrepreneurship serves as a multidimensional tool for ethnic minority women, not only improving economic outcomes but also enhancing agency and inclusion. Culturally embedded approaches are essential for effective support and empowerment. Policy interventions must move beyond generic economic frameworks and instead incorporate cultural sensitivity and tailored support systems. Strengthening community-based networks and ethical entrepreneurial ecosystems can significantly improve the sustainability and inclusivity of women-led enterprises.